The role of macrophages polarization in sepsis-induced acute lung injury - Wang, Ziyi; Wang, Zhong (Frontiers in Immunology, 2023)
Abstract: Sepsis presents as a severe infectious disease frequently documented in clinical settings. Characterized by its systemic inflammatory response syndrome, sepsis has the potential to trigger multi-organ dysfunction and can escalate to becoming life-threatening. A common fallout from sepsis is acute lung injury (ALI), which often progresses to acute respiratory distress syndrome (ARDS). Macrophages, due to their significant role in the immune system, are receiving increased attention in clinical studies. Macrophage polarization is a process that hinges on an intricate regulatory network influenced by a myriad of signaling molecules, transcription factors, epigenetic modifications, and metabolic reprogramming. In this review, our primary focus is on the classically activated macrophages (M1-like) and alternatively activated macrophages (M2-like) as the two paramount phenotypes instrumental in sepsis' host immune response. An imbalance between M1-like and M2-like macrophages can precipitate the onset and exacerbate the progression of sepsis. This review provides a comprehensive understanding of the interplay between macrophage polarization and sepsis-induced acute lung injury (SALI) and elaborates on the intervention strategy that centers around the crucial process of macrophage polarization.